Community-Onset Methicillin-Resistant Staphylococcus aureus Associated with Antibiotic Use and the Cytotoxin Panton-Valentine Leukocidin during a Furunculosis Outbreak in Rural Alaska - Baggett, Henry C.; Hennessy, Thomas W.; Rudolph, Karen; Bruden, Dana; Reasonover, Alisa; Parkinson, Alan; Sparks, Rachel; Donlan, Rodney M.; Martinez, Patricia; Mongkolrattanothai, Kanokporn; Butler, Jay C. (The Journal of infectious diseases, 2004)
Background. Community-onset methicillin-resistant Staphylococcus aureus (CO-MRSA) reports are increasing, and infections often involve soft tissue. During a CO-MRSA skin infection outbreak in Alaska, we assessed risk factors for disease and whether a virulence factor, Panton-Valentine leukocidin (PVL), could account for the high rates of MRSA skin infection in this region. Methods. We conducted S. aureus surveillance in the outbreak region and a case-control study in 1 community, comparing 34 case patients with MRSA skin infection with 94 control subjects. An assessment of traditional saunas was performed. S. aureus isolates from regional surveillance were screened for PVL genes by use of polymerase chain reaction, and isolate relatedness was determined by use of pulsed-field gel electrophoresis (PFGE). Results. Case patients received more antibiotic courses during the 12 months before the outbreak than did control subjects (median, 4 vs. 2 courses; P=.01) and were more likely to use MRSA-colonized saunas than were control subjects (44% vs. 13%; age-adjusted odds ratio, 4.6; 95% confidence interval, 1.7–12). The PVL genes were present in 110 (97%) of 113 MRSA isolates, compared with 0 of 81 methicillin-susceptible S. aureus isolates (P<.001). The majority of MRSA isolates were closely related by PFGE. Conclusion. Selective antibiotic pressure for drug-resistant strains carrying PVL may have led to the emergence and spread of CO-MRSA in rural Alaska.